Policy actors' perceptions of public participation to tackle health inequalities in Scotland: a paradox? - Neil McHugh; Rachel Baker; Clare Bambra (BMC, 2023)
Abstract Background Health inequalities are persistent and widening with transformative policy change needed. Radically shifting policy to tackle upstream causes of inequalities is likely to require public participation to provide a mandate, evidence and to address questions of co-design, implementation and acceptability. The aim of this paper is to explore perceptions among policy actors on why and how the public should be involved in policymaking for health inequalities. Methods In 2019-2020, we conducted exploratory, in-depth, semi-structured interviews with 21 Scottish policy actors from a range of public sector bodies and agencies and third sector organisations that work in, or across, health and non-health sectors. Data were analysed thematically and used to examine implications for the development of participatory policymaking. Results Policy actors viewed public participation in policymaking as intrinsically valuable for democratic reasons, but the main, and more challenging, concern was with how it could affect positive policy change. Participation was seen as instrumental in two overlapping ways: as evidence to improve policies to tackle health inequalities and to achieve public acceptance for implementing more transformative policies. However, our analysis suggests a paradox: whilst policy actors place importance on the instrumental value of public participation, they simultaneously believe the public hold views about health inequalities that would prevent transformative change. Finally, despite broad agreement on the need to improve public participation in policy development, policy actors were uncertain about how to make the necessary changes due to conceptual, methodological and practical challenges. Conclusions Policy actors believe in the importance of public participation in policy to address health inequalities for intrinsic and instrumental reasons. Yet, there is an evident tension between seeing public participation as a route to upstream policies and a belief that public views might be misinformed, individualistic, short-term or self-interested and doubts about how to make public participation meaningful. We lack good insight into what the public think about policy solutions to health inequalities. We propose that research needs to shift from describing the problem to focusing more on potential solutions and outline a potential way forward to undertake effective public participation to tackle health inequalities.